Insects : a guide to familiar American insects - Zim, Herbert S. (Herbert Spencer), 1909-1994.; Cottam, Clarence, 1899-; Irving, James Gordon (New York : Golden Press, 1956)
A guide to North American insects which gives popular name, describes life and reproduction cycles and feeding habits, and includes a range guide.
Includes index.
Keywords: Insects -- North America; Insects -- North America